Core–shell Au/CeO2 nanoparticles supported in UiO-66 beads exhibiting full CO conversion at 100 °C. Issue 27 (29th June 2017) - Yazdi, A.; Abo Markeb, A.; Garzón-Tovar, L.; Patarroyo, J.; Moral-Vico, J.; Alonso, A.; Sánchez, A.; Bastus, N.; Imaz, I.; Font, X.; Puntes, V.; Maspoch, D.
Abstract : Hybrid core–shell Au/CeO2 nanoparticles (NPs) dispersed in UiO-66 shaped into microspherical beads are created using the spray-drying continuous-flow method. Abstract : Hybrid core–shell Au/CeO2 nanoparticles (NPs) dispersed in UiO-66 shaped into microspherical beads are created using the spray-drying continuous-flow method. The combined catalytic properties of nanocrystalline CeO2 and Au in a single particle and the support and protective function of porous UiO-66 beads make the resulting composites show good performances as catalysts for CO oxidation ( T 50 = 72 °C; T 100 = 100 °C) and recyclability.